FORMATION OF PROFESSIONAL LINGUISTIC COMPETENCY OF FOREIGN MEDICAL STUDENTS AT UKRAINIAN LANGUAGE CLASSES - Tsurkan, Maria (Continuing Professional Education: Theory and Practice, 2019)
Formation of professional competence in the process of becoming a future doctor needs an interdisciplinary substantiation of integrated model, improvement of content, forms and methods of teaching, creation of favorable psychological and educational conditions of practical training activities. The article outlines the concept of professional language competence of a foreign medical student and suggests effective methods of mastering Ukrainian medical terminology as an essential component of professional competence. The methodical system as a combination of effective methods of forming professional language competence of a future physician is described on the example of studying the communicative theme «Blood. Blood Donors». The criteria of evaluation of student achievements, the state of formation of professional knowledge, skills and abilities, values orientations, culture of speech, style of communication are determined. The basic principles of the formation of professional linguistic competence are such as dominance of communicative approach and professionally oriented content «Ukrainian as a foreign language», the systemic principle in preparation of tasks for all types of speech activity (reading, speaking, listening, writing), the principle of adaptation educational materials for communicative needs of medical students. The four-component structure of professional language competence of a foreign doctor is described. In particular, the following four components are identified: informative (defining ways of perception, storage and transmission of information), analytical (including comparison, classification, abstraction, forecasting, systematization and specification of linguistic material); communicative (through which the information is transmitted, that is, there is a communicative interaction), social (realization of social roles of a foreign student at «student–teacher» and «student–physician-patient» levels).